Chronic endometritis in women with endometriosis-associated infertility - Mekan R. Orazov; Victor E. Radzinsky; Snezhana V. Volkova; Marina B. Khamoshina; Ludmila M. Mikhaleva; Marianna Z. Abitova; Victoria B. Shustova (IP Berlin A.V., 2020)
The article highlights modern ideas about the role of the endometrium in the genesis of reproductive failures. A crucial place of chronic endometritis in the structure of the endometrial infertility factor in endometriosis is noted. Given the frequent association of chronic endometritis and endometriosis, common features of these diseases have been identified. The characteristic of endometrial microbiota in infertility, chronic endometritis and endometriosis is given. An extremely important area of scientific research is precisely the interaction between the microbiota of the endometrium and its immunity, and not just the confirmation of the presence of microorganisms in the endometrium. The modern aspects of the etiology and pathogenesis of chronic endometritis and endometriosis are described. The main pathogenetic determinants of chronic endometritis are the failure of adaptation mechanisms to the constant effects of microbes and, as a consequence, the decrease and inferiority of the immune response and the development of autoimmune reactions. The modern paradigm for the development and progression of endometriosis involves the presence of bacterial contamination of the endometrium and the abdominal cavity, which in turn becomes a trigger for genetically-epigenetic modifications of cells, launching different cascades that underlie reproductive function disorders. The pathogenetically significant relationship between chronic endometritis and endometriosis is highlighted. It was revealed that chronic endometritis can be both a cause and a consequence of endometriosis. Disorders of the endometrial receptivity in chronic endometritis associated with endometriosis, their importance in the implementation of endometrial infertility are described. The important role of the microbiome in the formation of reproductive disorders is noted.